RETRACTED ARTICLE: Oxytocin versus a combination of tranexamic acid and ethamsylate in reducing intraoperative bleeding during abdominal myomectomy: a randomized clinical trial - Ahmed Mahmoud Abdou; Elsayed Eldesouky; Elsayed Farag; Attia Mohammed; Doaa Fathy Mohamed Abdelaziz; A. Shaaban; Mostafa Ellaban; Abd Elhalim Mohamed Abd Elhalim; Ahmed Gamal Abo Elsror; Alrefaai Abd Elfattah Marai; Faiza Abdel-Hakam; Mohamed Abd-ElGawad; et al. (BMC, 2023)
Abstract Objective Myomectomy is the preferred surgical approach to manage uterine fibroids. However, uterine fibroids are highly vascular tumors and, consequently, extremely susceptible to problems from myomectomy-related hemorrhage. Hence, we aim to compare oxytocin efficacy and safety profile versus tranexamic acid (TA) with ethamsylate for reducing bleeding during myomectomy. Methods This randomized, double-blinded multicenter study was performed between 20th August 2020 and 20th October 2020 at El-Galaa Teaching Hospital, El Hussein University Hospital, Al-Azhar University Hospitals of Assiut, and Al-Azhar University Hospitals of Damietta. One hundred and eighty patients were enrolled and divided into three groups: group (1) received an injection of 30 IU of oxytocin in 500 ml of normal saline; group (2) received injections of 1 g of TA, 250 mg of Ethamsylate, and 110 ml of normal saline IV; and group (3) received an injection of 110 ml of normal saline IV just before surgical incision. Results In 180 premenopausal women, oxytocin and TA with ethamsylate had no significant value in lowering intraoperative blood loss compared with the placebo for abdominal myomectomy (666.25 ± 183.03, 630.72 ± 145.83, and 646.67 ± 168.92, respectively (P = 0.506)). Non-significant trends were observed for a reduction in operation time (P = 0.760), intra/postoperative blood transfusion (P = 0.624), hospital stay (P = 0.986), postoperative fever (P = 0.659), and wound infection (P = 1). Conclusion Oxytocin and TA with ethamsylate had no significant value in lowering intraoperative blood loss compared with the placebo for abdominal myomectomy which opens a new question about the role of the use of the hemostatic drug during myomectomy especially in centers with limited resources and had higher rates. Trial registration The study was registered on Pan African Clinical Trials Registry with the following number: PACTR202008739887429 and was approved on 24/08/2020.